Trends in wireless communication and information security proceedings of EWCIS 2020 ; 8-9 October, 2020, Ranchi, India - Chakraborty, Mithun; Jha, Raman Kr.; Balas, Valentina Emilia; Sur, Samarendra Nath; Kandar, Debdatta; International Conference on Emerging Wireless Communication Technologies and Information Security (Singapore Springer, 2021)
This book presents best selected papers presented at the International Conference on Emerging Wireless Communication Technologies and Information Security (EWCIS 2020), held from 8th & 9th October 2020 at Amity University Jharkhand, Ranchi, India. The book includes papers in the research area of wireless communications and intelligent systems, signal and image processing in engineering applications, data communication and information security, IoT and cloud computing. The contribution ranges from scientists, engineers and technologists from academia as well as from industry.
Free Space Optical Communications to Connect the Unconnected Globally in Remote Places: Technology Issues Relevant to Implementing Systems A Study of Black Hole Attacks in Delay Tolerant Network A Survey on Open-Source Scada for Industrial Automation Using Raspberry Pi Extended Microstrip Line fed Circularly Polarised Dielectric Resonator Antenna for WiMAX and 5G Applications PPM-SIM based FSO System under Various Environmental Conditions Single Layered Mantle Cover for Cloaking at Dual Frequencies in Antenna Application Optical Noise Cancellation using Artificial Neural Network Digital Chaos Encryption based Sub-block Partition by a Hybrid PTS Approach and PAPR Reduction using HSOSS Algorithm Millimeter Wave: A Novel Approach for Integrating Radar and Communication for Autonomous Driving Throughput Analysis of MIMO HetNet System with Lattice Reduction Aided Precoding
Electronic reproduction
Keywords: Wireless communication systems -- Congresses; Internet of things -- Congresses; Electronic books